應用遙測衛星地表溫度資料探討都市熱島現象與社經空間發展之關係 - 呂毓倫; Lu, Yu-Lun (2008)
都市化現象造成人口聚集的現象，因而產生密集的運輸旅次，排放大量汽機車廢氣造成空氣汙染等環境衝擊，都市中人工建築物與不透水層鋪面加重惡化都市內的空氣流通與水循環系統，使自然環境失去原本調節氣溫的?能，相對地又增加空調設備的能源損耗，這種都市氣溫遠高於周圍郊區之氣溫稱為「都市熱島效應」。近年來，台灣地區之都市熱島研究區域與觀測時間大多集中在台北市與乾燥的季節，內容則主要運用移動觀測法取得溫度資料分布，偏重都市熱島強度與都市人口規模或公園之綠色資源之間的關係。本研究運用遙測衛星技術為工具，以其具有時間同步與拍攝範圍廣的特點彌補原有研究的不足，以台南市為研究範圍，利用MODIS 感測器所拍攝之資料判讀出台南市地表溫度（LST）分布情況，輔以福衛二號拍攝影像所計算之常態化差異植生指標（NDVI）值進行空間解析度校正，並應用地理資訊系統（GIS）將台南市之社經變數資料，如土地使用類型、人口分佈密度、建築物比率、道路鋪面比率、綠覆率等套疊於地表溫度圖，藉以瞭解地表溫度圖於都市尺度中的分佈情形。研究發現在台南夏季白天的土地使用中以商業區平均地表溫度36 52℃為最高之分區使用，由本研究所建置之台南市都市熱島模型得知以「道路鋪面比率」與「建築物比率」為影響地表溫度最顯著之變數，而綠覆率為所選取變數中唯一能夠減緩地表溫度值上升的因子，由模型中綠覆率與道路鋪面比率以及建築物比率之彈性值0 64 及0 58，表示在同一里別中當增加一單位面積之建築物與道路鋪面所提高之地表溫度需增加該里約0 6 單位面積之綠覆面才能加以調節，且研究疊圖得知2007 年台南市公園與綠地之綠覆率為45%及41%，皆未能符合「台南市植栽綠化都市設計審議原則」所規定之最小綠覆率60%，因此未來台南市仍應增加相關綠覆率之政策執行以創造永續的生活環境。 Because of urbanization people gather and live in the city and thus make huge transportation trips Lots of vehicle exhausts cause air pollution but being full of artificial architectures and impervious pavements in urban environment make the air and water cycle systems worsen Nature environment decrease its function of adjusting the air temperature relatively increase the use of air conditions and higher energy consumption which derived the phenomenon “Urban Heat Island Effect；UHI” means the air temperature higher in urban surrounding than in rural space Recent years most researches of UHI in Taiwan are focusing on dry seasons in Taipei By motorcycle-traverse approaches they found the relationship between population scale or park greenery resources and UHI intensities This paper will take advantage of remote sensing techniques possesses the merit of time chronological and widely picturing range by finding the locations of the highest and the lowest temperature in Tainan with land surface temperature（LST）derived from MODIS （Moderate-resolution Imaging Spectroradiometer） Using NDVI（Normalization Difference Vegetation Index）from the image of FORMOSA-2 to calibrate and increase the spatial resolution of the LST map at the micro-level Finally overlaying GIS social-economic data such as land-use type density of population the ratio of architectures and green cover ratio with LST aims at examining how social-economic parameters influenced the distribution of surface temperature in urban scale During daytime in summer we have the highest average temperature 36 52℃ in commercial district Furthermore in our UHI model we found the Ratio of Road and Architecture are the most significant variables affecting LST and the Ratio of Green cover is the only variable that can mitigate UHI effect Comparing with the elastic of the Ratio of Green cover over Road and Architecture we can realize that when increasing one area-unit of architecture or road in a village we must also increase about 0 6 area-unit of green cover to cool down the surface temperature With overlaying technique we find that the ratio of Green on park and Greenland in Tainan is 45% and 41% which unqualified to the minimum ratio of green in “Urban Design Review Panel of Tainan” According to the results above we can provide suggestions for government to cool down the local highest temperature region by improving the ratio of green cover and create a more sustainable environment